25
(6) (1) + 3 = 2
(ii)
5
х
2
4
(iii) 4 +5(p-1) = 34
31
2
11
(v
)
2
3
(vi) 10 = 4 + 3(t + 2)
(iv) 0 = 16 + 4(m - 6)
5. Solve the following equations:
(a) (1) 2x - (3x + 8) = 2(5 - 2x) - 6
X-6 x - 4
(iii)
= 1 -
4 6
10
X
(ii) 0.3x - (0.8 -0.2x) = 0.2-0.5x
2
1
9
(10
5)
3
4
2
3x 7x
29 2x
(b)
(ii) 7(x - 2) -8(4 - 3x) = 47
10 25
25
5
ope.
hmm nman teman
SECTION C. Hots QUESTIONS
Solve:
3
6. (1) 2 (14x – 2)—-—{4x -(1-x)} = x +
- )(-5) + «x-1) = « + 3)
8
24/0g
Answers
Answered by
1
Answer:
This question is in wrong way!
Step-by-step explanation:
Please give the question in right way,so that I can answer...
Similar questions